Hippo Signaling: Emerging Pathway in Stress-Related Psychiatric Disorders? - Stepan, Jens; Anderzhanova, Elmira; Gassen, Nils C. (Frontiers in Psychiatry, 2018)
Discovery of the Hippo pathway and its core components has made a significant impact on our progress in the understanding of organ development, tissue homeostasis, and regeneration. Upon diverse extracellular and intracellular stimuli, Hippo signaling regulates stemness, cell proliferation and apoptosis by a well conserved signalling cascade, and disruption of these systems has been implicated in cancer as well as metabolic and neurodegenerative diseases. The central role of Hippo signaling in cell biology also results in prominent links to stress-regulated pathways. Genetic variations, epigenetically provoked upregulation of Hippo pathway members and dysregulation cellular processes implicated in learning and memory, are linked to an increased risk of stress-related psychiatric disorders (SRPDs). In this review, we summarize recent findings, supporting the role of Hippo signaling in SRPDs by canonical and non-canonical Hippo pathway interactions.